Matéria orgânica proveniente de água residuária de suinocultura na interação e transporte de alaclor no solo - Bosco, Tatiane Cristina Dal (2011)
Swine wastewater application into soil to reuse water on cropping provides the addition of total and dissolved organic matter to soil, which interferes in the dynamics of pesticides in soil. This study aims at evaluating the effects of total and dissolved organic matter application from two systems of swine wastewater, biodigestor and lagoon treatments, in alachlor sorption, desorption, leaching and formation of bound residues into soil. The batch method was used to test sorption and desorption and the results were presented in Freundlich isotherms. The evaluation of miscible displacement of alachlor, in soil treated with total and dissolved organic matter, was performed by disturbed soil columns, by monitoring the concentration of alachlor in leachate, total organic carbon and pH. Extraction and quantification of desorption, extractable and bound residues were carried out. After that, it was registered the chemical fractionation of humic substances in extracts containing organic matter of low molecular weight, humic acids and fulvic acids, which were characterized by infrared spectroscopy and total organic carbon concentration. The swine wastewater addition promoted greater sorption and desorption of alachlor compared to Control. The dissolved organic matter promoted less sorption of alachlor in soil when compared to total organic matter, resulting in an increased leaching of alachlor. The dissolved organic matter did not show desorption residues, only extractable ones. The highest amount of total organic carbon was in organic matter of low molecular weight, spectroscope characterized, by the presence of carboxylate anions, which are important in sorption process. The total organic matter has contributed to the emergence of new sorption sites in soil column and the solids present in its composition blocked the movement of pesticide, resulting in lower leaching of alachlor. The dissolved organic matter interacted with alachlor and / or competed with the sorption sites of soil, promoting greater losses by leaching of this herbicide.